A MENINGKATKAN KETAHANAN MASYARAKAT UNTUK LINGKUNGAN YANG KONDUSIF DALAM PROSES PEMILU 2024 - Sulistyowati, Sulistyowati; Bayu Mahendra, Viki; Fatuh Widoyo, Agus; Ivany, Zulkarnain; Nur Azizah, Ummi (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2024)
Community Service Activities (PkM) involve 2024 PKN-T IIM Surakarta students, especially the Danukusuman Subdistrict group, the Subdistrict Head and his staff, Danukusuman Subdistrict Bawaslu, Serengan Subdistrict Supervisor, Danukusuman Subdistrict Supervisor, and the Danukusuman Subdistrict community with the aim of increasing community resilience in facing 2024 election process. The subjects of assistance in this program are first-time voters and the public, especially ordinary people, in carrying out election voting procedures. This approach uses outreach, training and group discussions to build collective awareness of the importance of creating a safe and open environment during elections. Key achievements include increasing people's understanding of their active role in maintaining stability during elections, improving skills in dealing with potential conflicts, and strengthening social networks and solidarity between various segments of society. The implication of this activity is its contribution to increasing community resilience in facing the challenges of the 2024 elections, with the hope that this will have a positive impact on stability and a conducive atmosphere during the election period, as well as strengthening community involvement in the democratic process.